Factors influencing the failure of exclusive breastfeeding in infants aged 0-6 months in the batua community health center work area : a qualitative study - Marina, Marina (CV. Paperhome Indonesia, 2024)
Background: A quality young generation is an important asset for the future of the nation. Exclusive breastfeeding for the first six months of a baby's life is the main step to support optimal growth and development. However, the practice of exclusive breastfeeding in Indonesia still faces various obstacles, including social traditions, lack of education, and challenges in breast milk production. This study aims to explore the experiences of breastfeeding mothers in the Batua Health Center work area related to the practice of exclusive breastfeeding and the factors that influence it. Methods: This study used a qualitative phenomenological approach with in-depth interviews and participatory observations of 15 breastfeeding mothers, 2 husbands, 4 family members, and 1 village shaman. Data were analyzed using triangulation to ensure validity. Results: The findings show that the practice of exclusive breastfeeding is constrained by traditions such as giving honey, sugar water, or porridge from an early age. Other factors include insufficient breast milk production, family pressure, and lack of understanding of the benefits of exclusive breastfeeding. Most mothers also provide formula milk as an alternative. In addition, postpartum food taboos and local traditions affect the quality of breastfeeding. Conclusion: Intensive education from health workers and changes in social traditions are needed to increase exclusive breastfeeding rates. The government and health community should be more active in providing support, especially for mothers with challenges in breast milk production and social pressures, to support optimal infant health and development.